2018
DOI: 10.5194/acp-18-8601-2018
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D evaluation of the MACC reanalysis dust product over Europe, northern Africa and Middle East using CALIOP/CALIPSO dust satellite observations

Abstract: Published by Copernicus Publications on behalf of the European Geosciences Union. 8602A. K. Georgoulias et al.: A 3-D evaluation of the MACC reanalysis dust product low ∼ 3-5 km a.s.l. depending on the period of the year. In general, it is shown that dust loadings appear over remote regions and at heights up to 9 km a.s.l. in MACC contrary to LIVAS. This could be due to the model performance and parameterizations of emissions and other processes, due to the assimilation of satellite aerosol measurements over d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Thus, Wet_Dep improves the AOD bias score by slightly underestimating it; additionally, it reduces RMSE. Such improvements substantially correct the spatiotemporal distribution of the suspended dust throughout the simulation period and are contributing factors to the reduction of its well-known dust concentration overestimation problem [60,64,[76][77][78].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, Wet_Dep improves the AOD bias score by slightly underestimating it; additionally, it reduces RMSE. Such improvements substantially correct the spatiotemporal distribution of the suspended dust throughout the simulation period and are contributing factors to the reduction of its well-known dust concentration overestimation problem [60,64,[76][77][78].…”
Section: Discussionmentioning
confidence: 98%
“…A mean bias of 25% was found between MACC and LIVAS, a dust product based on CALIPSO observations over Europe, northern Africa and Middle East (Georgoulias et al, 2018). Additionally, the correlation between MACC and AERONET was found to range from 0.6 over the Sahara and Sahel to 0.8 over typical regions of dust transport (Cuevas et al, 2015).…”
Section: Macc and Era-interimmentioning
confidence: 90%
“…A minimum dust AOD value of 0.3 was set-where needed-in defining the areas impacted by dust to ensure the presence of dust in the atmosphere over the Hellenic Seas. Evaluations of the ECMWF/MACC (Monitoring Atmospheric Composition and Climate) AOD re-analysis at visible wavelengths against measurements and observations showed that it presents an overestimation when dust load is low especially during spring, summer and autumn and an underestimation for values >0.3 [60], while a root mean square difference from observations of about 0.25 was reported for Thessaloniki AERONET (AErosol RObotic NETwork) station [61]. In addition, during the summer and autumn events of the present study, PM10 values <50 were observed when the forecasted dust AOD was <0.25.…”
Section: Methodsmentioning
confidence: 99%